The Single Intradermal Cervical Comparative Test Interferes with Johne’s Disease ELISA Diagnostics - Kennedy, Aideen E.; Da Silva, Ana T.; Byrne, Noel; Govender, Rodney; MacSharry, John; O’Mahony, Jim; Sayers, Riona G. (Frontiers in Immunology, 2014)
Enzyme-linked immmunosorbent assays (ELISA) of milk and serum samples are a routinely used method of screening herds for Mycobacterium avium subspecies paratuberculosis (MAP). Infection with MAP causes a granulomatous enteritis of ruminants known as Johne’s disease (JD). The sensitivity (Se) and specificity (Sp) of MAP ELISAs leads to difficulties in the identification of both infected and infectious animals. Interference with MAP ELISA Se and Sp has been reported in MAP seronegative cows following administration of purified protein derivative (PPD) as part of intradermal testing for bovine tuberculosis (bTB). The aim of this study is to examine the impact of the single intradermal cervical comparative test (SICCT) for bTB, on both serum and milk MAP ELISA tests, in a herd containing both seropositive and seronegative cows pre- SICCT. A secondary objective is to provide appropriate timing of JD ELISA tests in relation to the SICCT. A herd of 139 cows were serum and milk sampled pre and post SICCT administration. Prior to SICCT, 6% of the herd tested seropositive for MAP using milk ELISA, with 8% positive on serum. ID Screen Paratuberculosis Indirect Screening Test (ID Vet) was used to screen the herd. Within 14 days of PPD administration, a significant increase in the prevalence of seropositive cows was recorded. Identical prevalence’s were recorded with both test matrices (39%). ELISA values remained significantly higher until day 43 post-SICCT in milk (P=0.850), and day 71 in serum (P=0.602). If the ‘new’ positives detected post-bTB testing are deemed false positives due to generation of cross-reacting antibodies by administration of PPD, milk would appear a more suitable sample for JD ELISA testing within two months of SICCT. In summary, sampling for JD utilising milk ELISA should be avoided in the 43 day period following PPD administration, with serum ELISA sampling avoided for an additional 28 days.